Determinants of business performance of small and medium enterprise: A study on maruthamunai area - Muthusamy, V.; Amitha, W.A.K.; Saajith, M.A.C.A. (University of Jaffna, 2020)
Small and Medium Enterprises are the real backbone of all economies globally and a key source of economic growth, innovation, employment generation and poverty reduction. The country like Singapore has achieved its success as they focused more on SMEs. More than 90% of ventures in Singapore accounts for SMEs. In Sri Lanka, it is just 75% and provides just 45% of job opportunities. Hence, SMEs' contribution towards the economy is significantly low and there is a doubt about the performance level of SMEs of Sri Lanka. Accordingly, this study aims to investigate the factors affecting SMEs' business performance in the Maruthamunai area, Sri Lanka. The study was conducted based on positivism philosophy and deductive approach was executed. Further, the current study is an exploratory cross-sectional study and data were gathered by deploying a survey method. In this study, SMEs' business performance was used as the dependent variable and factors influencing the business performance of SMEs were used as independent variables. The target population was 469 SMEs registered in Kalmunai Municipal Council in Ampara district, Sri Lanka and sample selection was based on judgmental sampling method. Out of the total population of 469 there was 80 sample was selected. Data was gathered using structured questionnaires. Data were analysed by using IBM SPSS. This study used correlation and multiple regression models to analyse the collected data. There were five independent variables statistically significants with business performance. Namely; needs for achievement, entrepreneurial competencies, regulatory environment, technology, and information and two variables were insignificant with business performance. Namely; risk-taking propensity and managerial competencies. Hence, this study's findings can be used to make proper decisions to improve the performance level of SMEs in Sri Lanka.
Keywords: Business performance; External factors; Internal factors; Small and medium enterprises (SMEs)